Drug therapies used in the treatment of Covid-19 in Brazil: narrative bibliographic review (Research, Society and Development, 2021)
Objective: To present an overview of the pathophysiology of Covid-19 and drug treatments used in Brazil. Methodology: This is a narrative bibliographic review. Searches were performed on official websites (Ministry of Health of Brazil; Butantan); Cochrane, Google Scholar, Pubmed and Scielo databases and supplementary texts. Searches took place between February and June 2021 under the terms 'Covid-19', 'Coronavirus' 'Pandemia', 'Covid-19 vaccines', 'SARS-CoV-2' and 'Covid-19 drug therapies'. Texts in English, Portuguese and Spanish, published from 2020, were included and texts that were not related to the theme were excluded. Results: Azithromycin, corticosteroids, antiretrovirals and anticoagulants exemplify drugs used in the treatment of Covid-19, in addition to prevention with vaccines. Conclusion: During the period of this review, the effort of the scientific community in the repositioning of drugs to treat the disease was noted, but no evidence was found to prove the effectiveness of a specific treatment. Vaccines become a great ally in preventing the disease.